The Relevance of Maternal Socioeconomic Characteristics for Low Birth Weight – a Case-Control Study - Altenhöner, T.; Köhler, M.; Philippi, M. (Geburtshilfe und Frauenheilkunde, 2016)
Introduction: The number of children born underweight (low birth weight, LBW) is increasing despite extensive prevention and screening programmes. The cost is high for the health system, and affected children are burdened with health predictors that can affect them negatively throughout their lives. This study investigates to what extent socioeconomic factors, in addition to known medical causes and the health behaviour of pregnant women, influence LBW. Materials and Methods: In this case-control study 131 mothers of singletons with a birth weight ≤ 2500 g (cases) and 323 mothers of normal birth weight babies (controls) were interviewed with respect to socioeconomic status, health behaviour and stress in the workplace. Medical data were collected by specialist staff using a questionnaire. Results: Independent of medical diagnosis and health behaviour, women with lower level education (OR [95 % CI] = 2.24 [1.12; 4.51]) and those who were not working (OR [95 % CI] = 1.82 [1.10; 3.00]) were more likely to have an LBW baby. No effect was shown for immigrant background (OR [95 % CI] = 1.14 [0.59; 2.21]) or stress in the workplace (OR [95 % CI] = 1.17 [0.90; 1.51]). Discussion and Conclusion: These results show that the association between social and health inequalities starts from before birth. In order to reduce the rising number of babies born underweight, socioeconomic determinants in the care and supervision of pregnant women should systematically receive more attention to enable appropriate early preventive strategies to be implemented.
Keywords: low birth weight; preterm birth; health inequalities; social inequalities; case-control study